Измерение тока кондуктивных радиопомех - Немченко, Юрий Семенович; Животов, Н. Д.; Сараев, А. И.; Островерх, Т. Н. (НТУ "ХПИ", 2014)
Описана современная методика измерения эмиссии тока радиопомех от бортового авиационного оборудования с помощью токосъемника ТС-А, созданного и прокалиброванного в Испытательной лаборатории НИПКИ «Молния». Эта методика позволяет быстро и эффективно определить: выполняются ли в испытываемом изделии требования по эмиссии токов радиопомех по всем действующим в Украине нормативным документам в полном объеме. Требования стандарта ДСТУ IEC 61000-4-6:2007 являются обязательными к выполнению в Украине.

Modern methodology of measuring of emission of current of radio interferences is described from the on-board aircraft equipment by means of current monitoring transformer ТS-А, created and calibrated in the Test laboratory of Research & Design Institute «Molniya». This methodology allows quickly and effectively to define: whether executed in the tested good of requirement on emission of currents of radio interferences on all operating in Ukraine normative documents in full. The standard requirements of DSTU IEC 61000-4-6: 2007 are required to perform in Ukraine.
Measuring of emission of current of radio interferences
Keywords: эмиссия; токосъемник; бортовое авиационное оборудование; current monitoring transformer; on-board aircraft equipment